Research Path on AAOIFI Standards Studies - Firmansyah, Irman (Review on Islamic Accounting, 2025)
The standards developed by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) play a strategic role in shaping the governance, accountability, and transparency of Islamic financial institutions at the global level. This research aims to map the development of research related to AAOIFI Standards and elaborate on the main themes that appear in the academic literature. The methods used were bibliometric analysis and keyword mapping of scientific publications with the theme of AAOIFI Standards, which were then analyzed descriptively and thematically. The results of the study show six main clusters, namely: (1) Islamic banking governance and AAOIFI Standards, (2) accountability and sustainability of Islamic financial standards, (3) global Islamic accounting standards, (4) harmonization of Islamic financial law, (5) regulation of Islamic banking standards, and (6) transparency of Islamic financial reporting. These findings confirm that AAOIFI not only functions as a technical accounting guideline, but also as an instrument for governance, regulatory harmonization, and strengthening sustainability and public trust in the Islamic financial system. This research makes a conceptual contribution to the development of Islamic financial literature and policy implications for regulators and practitioners of Islamic financial institutions.